2020
DOI: 10.1021/acssuschemeng.0c06345
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient CO2 Capture Using Nonaqueous Absorbents of Secondary Alkanolamines with a 2-Butoxyethanol Cosolvent

Abstract: Nonaqueous amine-based absorbents by replacing water with organic solvents have potential advantages of low energy penalty and reduced amine degradation for CO 2 capture. An advanced nonaqueous system of 2-(butylamino)ethanol (BAE) with 2-butoxyethanol (EGBE) was proposed for low-energy consumption CO 2 capture. EGBE was selected as a green cosolvent because of its superior properties over the reported organics and water. A comprehensive study on CO 2 capture performance has been performed for secondary alkano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…investigated the absorption–desorption cycles with 0.5 M DETA/NMP using microwave heating, and the results showed that the system had a relatively stable cycling performance. Ping et al 27 . reported that the regeneration energy consumption of nonaqueous 2‐(butylamino)ethanol (BAE)/2‐butoxyethanol (EGBE) was significantly reduced to about 1.73 MJ kg –1 CO 2 , which is about 55% lower than that of aqueous MEA under the same operating conditions using microwave heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…investigated the absorption–desorption cycles with 0.5 M DETA/NMP using microwave heating, and the results showed that the system had a relatively stable cycling performance. Ping et al 27 . reported that the regeneration energy consumption of nonaqueous 2‐(butylamino)ethanol (BAE)/2‐butoxyethanol (EGBE) was significantly reduced to about 1.73 MJ kg –1 CO 2 , which is about 55% lower than that of aqueous MEA under the same operating conditions using microwave heating.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Zhang et al 26 investigated the absorption-desorption cycles with 0.5 M DETA/NMP using microwave heating, and the results showed that the system had a relatively stable cycling performance. Ping et al 27 reported that the regeneration energy consumption of nonaqueous 2-(butylamino)ethanol (BAE)/2-butoxyethanol (EGBE) was significantly reduced to about 1.73 MJ kg -1 CO 2 , which is about 55% lower than that of aqueous MEA under the same operating conditions using microwave heating. Li et al 28 investigated the characteristics of microwave regeneration for nine TETA nonaqueous solutions at 0.6 M, and the results showed that the heating rate of a solution in the microwave was primarily affected by its viscosity, dielectric constant, and heat capacity.…”
mentioning
confidence: 99%
“…5−11 In comparison to MEA, secondary alkanolamines, 2-(methylamino)ethanol (MAE), with a methyl group connected to a N atom show comparative reaction kinetics, lower heat of absorption, larger CO 2 capacity, and enhanced stability. 8,12 DMSO, as a highly polar organic solvent, has lower volatility and specific heat capacity than water. 13 In addition, it also has relatively low viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…However, high energy consumption for solvent regeneration in the capture process prevents its large-scale implementation . Water-lean amine absorbents by partially replacing water with organic solvent have been proved to be a promising solution for energy-efficient CO 2 capture. , Recently, there has been a large number of studies on absorbent formulation and its CO 2 capture performance in this area. In comparison to MEA, secondary alkanolamines, 2-(methylamino)­ethanol (MAE), with a methyl group connected to a N atom show comparative reaction kinetics, lower heat of absorption, larger CO 2 capacity, and enhanced stability. , DMSO, as a highly polar organic solvent, has lower volatility and specific heat capacity than water . In addition, it also has relatively low viscosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation